Readers perceive deceptive graphics as less credible. (December 2017) - Geidner, Nick; Cameron, Jaclyn
This study examines individuals' understanding and judgment of news information graphics. Specifically, an experimental design was used to examine the effects of deceptive design practices on the amount of time the user spent on the graphic, information recall and perceptions of credibility. These effects were examined in a general and political news context. In the sample (N = 239), participants recalled more information from the deceptive graphic and found it less credible than the non-biased graphic.